Gambaran Kualitas Hidup Family Caregiver Penderita Skizofrenia - Besse Widah Faridah; Ahmad Ridfah; Kartika Cahyaningrum (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Caring for person with schizophrenia (ODS) is a complex role with various challenges arises during treatment. Positive and negative symptoms of schizophrenia causes strain on family caregivers related to quality of life conditions. This study aims to overview the quality of life towards family caregivers of ODS through the domains of quality of life as caregivers. A qualitative study with a case study approach was adopted. Respondents of this study involved two family caregivers and two significant others selected based on purposive sampling. Data were collected by semi-structured interview derived from domains in the Adult Carer Quality of Life. The findings showed quality of life formed based on eight domains of quality of life, such as support for caring, caring choice, money matters, sense of value, personal growth, ability to care, and carer satisfaction. Family caregiver indicates various negative reactions during the first time of caregiving. However, along with the knowledge and experience of caring, family caregivers could performed positive perception of several aspects of quality of life. The impact of caregiving consists psychological, physical, social and financial from their caring role. The implication of this study is an understanding of the need of improvement of the quality of life among family caregivers of ODS, especially domains of caring stress, carer satisfaction, lack of caring support, and care ability.